Study of Constrained Velocity Inversion of Seismic Data in North Sumatra Basin - Tabah Fatchur Rubiyana; Budi Eka Nurcahya (Journal of Engineering and Technological Sciences, 2021)
Interval velocity analysis increases the precision of seismic velocity data with a complex structure and a high variation of velocity both laterally and vertically. In this study, interval velocity analysis was performed by applying the exponential asymptotically bounded function approach. An exponentially asymptotically bounded function was applied to calculate the interval velocity obtained from the root mean square velocity of seismic data using the Dix equation for conversion. To control this operation, a velocity constraint was applied in the interval velocity conversion. The velocity constraint used was the velocity trend gained from the root mean square velocity. This method is called constrained velocity inversion. In this study, interval velocity analysis using constrained velocity inversion was applied to seismic data from the North Sumatra Basin area. The seismic data interpretation resulted from the interval velocity analysis using constrained velocity inversion described the subsurface structure clearly. A corresponding anomaly at a time depth from 2000 ms to 2400 ms in the seismic time-domain data indicated a fault beneath an anticline. This result indicates that the interval velocity analysis of seismic data is more rigorous than the root mean square velocity analysis.